ADRENAL GLAND AND ITS FUNCTION (Multidisciplinary Journal of Science and Technology, 2024)
In this article, the anatomical, physiological and histological structure of the adrenal gland. Connection of kidney and adrenal gland. Fundamental study of the hormones produced by the adrenal gland and their mechanisms of action. Adrenal blood supply and control by the nervous system. Elucidation of the prevention and treatment of these diseases and its benefits.